Perlindungan Hukum PT Pegadaian (Persero) Selaku Kreditur Aras Barang Curian Dijadikan Jaminan Gadai (Studi Putusan Nomor 517/Pid.B/2023/PN SMG) - Purwanto, Windy Hanifah; Silviana, Ana (Universitas Ekasakti, 2023)
An economy that continues to develop in line with society's current needs. Loans using a pawn system are one of the alternatives chosen for distributing financing funds. However, in practice, there is still the practice of pawning credit systems with goods obtained from criminal acts, which is detrimental to PT Pegadaian (Persero) as the creditor of the pawnbroker. The method used in this research is Normative-Empirical with a qualitative descriptive approach. The results of the research show that, the position of PT Pegadaian (Persero) in this case as a creditor who gave the pawn, even though the collateral originates from a crime, namely, theft, does not necessarily make the company's position as a custodian. This is strengthened by the applicable laws and regulations and based on the considerations of the property judge. the guarantee is returned to PT Pegadaian (Persero). The anticipatory solution for PT Pegadaian (Persero) is that the company can reaffirm the regulations regarding the inclusion of collateral documents such as receipts for purchasing gold jewelry. Or it can be confirmed through a third party regarding ownership of the collateral. Next, the customer needs to make a statement as well as a power of attorney and approval for the goods to be guaranteed from the actual owner of the goods.